Exploring the Impact of the COVID-19 Pandemic on Patients with Type 2 Diabetes and Primary Care Utilisation: A Scoping Review - Irantzu Bengoa-Urrengoechea; Sara Malo; María José Rabanaque; María Antonia Sánchez-Calavera; Isabel Aguilar-Palacio (Healthcare, 2026)
Background: During the coronavirus disease 2019 (COVID-19) pandemic, changes in healthcare organisation may have affected the management of patients with chronic conditions, such as those with type 2 diabetes (T2D), who require close monitoring. Although there are studies that have analysed the access and management of patients with T2D in primary care (PC) during the pandemic, there is no synthesis of the results that inform us about the care provided and their effect. The aim of this study is to summarise the existing evidence on the care provided in PC settings to patients with T2D during the COVID-19 pandemic, as well as their follow-up care and outcomes, in order to understand the impact of the pandemic on their management. Methods: A scoping review was conducted according to the approach described by Arksey and O’Malley. Structured search strategies were developed for each of the selected databases (PubMed, EMBASE and Web of Science). We included articles published in English and Spanish up to 24 March 2026 on access to care for patients with T2D in PC during the pandemic. Two independent reviewers screened titles and abstracts to select studies related to the population, intervention, and outcomes of interest. In cases of disagreement, a third reviewer resolved the discrepancy. One of the reviewers extracted data and summarised them. Results: After duplicate removal, 535 records were identified, with 116 articles screened in full text and 26 included. Most studies were conducted in Europe and North America using retrospective designs and electronic health records. During the pandemic period, face-to-face visits and routine screenings generally declined, while telemedicine expanded and may have partially mitigated disruptions in patient contact, although inequalities in access were reported. Disease monitoring and complication screening also declined in several settings. Clinical outcomes such as HbA1c and blood pressure (BP) showed heterogeneous trends, with some studies reporting deterioration and others reporting stability. Some studies also highlighted increased adverse events and greater attention to mental health during care. Conclusions: Although telemedicine helped maintain patient follow-up, it could not fully replace face-to-face assessments and was implemented alongside some gaps in clinical monitoring, patient safety, and health equity. These findings underscore the need to maintain structured chronic disease management and to develop safe and inclusive telehealth models.